Determination of Water Evaporation Rates in Gas Diffusion Layers of Fuel Cells. Issue 9 (1st January 2018) - Lal, Sreeyuth; Lamibrac, Adrien; Eller, Jens; Büchi, Felix N.
Abstract : The efficiency of polymer electrolyte fuel cells is closely linked to effective heat and water management. Evaporation of water in the gas diffusion layers (GDL) is an important process influencing water management and can even be used for evaporative cooling. In this study, evaporation rates in Toray-GDL materials are obtained for different temperatures, gas flow rates, carrier gases and water saturation levels. Evaporation rates are correlated with water distribution profiles in the GDL, obtained using X-ray tomographic microscopy imaging. The influence of temperature on the evaporation rates is predicted by considering the effect of temperature on vapor diffusion alone. However, changing the carrier gas type points to a deviation from diffusive-driven vapor transport, which could be due to entrainment of gas inside the GDL, among other factors.